THE GRAMMAR OF INTERPERSONAL EXCHANGES COMMUNICATIVE ACTS USED IN EFL CLASS - Dwiniasih, Dwiniasih (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
The language structures of standard English may change for some local area. Such as, Malaysia, Singapore and it involves Indonesia. We have to dig deeper understanding of the language used, especially for the ungrammatical utterance both spoken or written. It has also been tried by teachers while they are guided the students in class by varying and modifying the learning technique or method used. In fact, the grammatical processes and illocutionary acts are still found during speaking activity. This study aims to analyse the clause used in EFL class in which mood and speakerâs intent do not match while speaking and identify the exact meaning of it. The findings show the declarative, interrogative, or imperative clause of mood has other Illocutionary acts used during speaking that was for directive, providing a threat, exclaiming, giving command, advice and conveying a negative statement. This result is supported by the generalization of mood of clause to the speakerâs act that relate to the local language structure and its meaning which has differences with standard English.Keywords:Functional grammar, Interpersonal exchanges, Communicative acts